Hambatan Bantuan Hukum Bagi Terdakwa Dalam Proses Peradilan Pidana Di Pengadilan Negeri Padang Kelas IA - Malverino Fitrah Laksana (RIO LAW JURNAL, 2021)
The right to a fair and impartial trial is a basic right of every human being. This right is universal, applies anywhere, anytime and to anyone without discrimination. This has been stated in the 1945 Constitution which states that everyone has the right to recognition, guarantee, protection and legal certainty that is just and equal treatment before the law. Based on these provisions, everyone has the right to a fair and impartial court. Legal aid is believed to be one of the means and efforts to create a fair trial process. However, the legal problem or legal problem that the author wants to examine is the lack of seriousness in the practice of justice, especially criminal justice. One of them is only as a formality, even though these rights and obligations are to defend from the side of legal certainty and justice. Therefore, examining the sociological reasons for the benefits of legal aid for the defendant, namely legal aid only as a formality without providing meaningful defense in every examination and examining the practices that should be carried out in legal aid in order to provide legal benefits and certainty to legal aid recipients, especially the defendant in obtaining legal assistance. in the Padang District Court Class IA. This research uses an empirical juridical approach, namely the method of approaching the problem by looking at the positive law that applies normatively by connecting the reality in the field, this research uses interview techniques and collects data and tables and is processed by the editing process. Based on the results of research conducted in the jurisdiction of the Padang Class IA District Court, the obstacles for the defendant to obtain legal assistance in the jurisdiction of the Padang Class IA District Court are the imbalance between the number of justice seekers and lawyers or legal aid providers, the number of legal aid providers is insufficient, the process for Obtaining legal assistance is difficult, as for the obstacles we encountered during the process of assisting the defendant, namely the difficulty of communicating with the defendant, constraints in finance or funds, because it requires costs or funds to summon expert witnesses in the examination of witnesses in criminal cases. It is recommended for Advocates to carry out the provision of legal aid even though the legal advisors are still insufficient or inadequate. Keywords: Barriers to Legal Aid, Defendant, Criminal Court.       AbstrakHak untuk memperoleh peradilan yang adil dan tidak memihak merupakan hak dasar setiap manusia.Hak ini bersifat universal, berlaku di manapun, kapanpun dan pada siapapun tanpa ada diskriminasi. Hal ini sudah tertuang ke dalam Undang-undang Dasar 1945 yang menyatakan bahwa setiap orang berhak atas pengakuan, jaminan, perlindungan, dan kepastian hukum yang adil serta perlakuan yang sama di hadapan hukum. Berdasarkan ketentuan ini, maka setiap orang berhak mendapatkan peradilan yang adil dan tidak memihak (fair and impartial court).Bantuan hukum dipercayai sebagai salah satu sarana dan upaya untuk terwujudnya proses peradilan yang adil (fair trial). Akan tetapi masalah hukum atau legal problem yang penulis ingin mengkaji adalah adanya ketidak seriusan dalam praktek peradilan khususnya peradilan pidana. Salah satunya hanya sebagai formalitas, padahal hak dan kewajiban ini  adalah untuk membela dari sisi kepastian hukum dan keadilan. Oleh sebab itu mengkaji alasan sosiologis dari manfaat bantuan hukum bagi terdakwa yaitu bantuan hukum hanya sebagai formalitas tanpa memberikan pembelaan berarti dalam setiap pemeriksaan dan mengkaji praktek yang seharusnya dilakukan dalam bantuan hukum agar memberikan manfaat dan kepastian hukum kepada penerima bantuan hukum khususnya terdakwa dalam memperoleh bantuan hukum di Pengadilan Negeri Padang Kelas IA.Penelitian ini menggunakan metode pendekatan yuridis empiris, yaitu metode pendekatan masalah dengan melihat hukum positif yang berlaku secara normatif dengan menghubungkan kenyataan di lapangan, penelitian ini menggunakan teknik wawancara dan mengumpulkan data dan tabel serta diolah dengan proses editing. Berdasarkan hasil penelitian yang dilakukan di wilayah hukum Pengadilan Negeri Padang Kelas IA, hambatan bagi terdakwa dalam memperoleh  bantuan hukum di wilayah hukum Pengadilan Negeri Padang Kelas IA adalah  tidak seimbangnya jumlah pencari keadilan dengan advokat atau pemberi bantuan hukum, jumlah pemberi bantuan hukum kurang, proses untuk mendapatkan bantuan hukum itu susah, adapun kendala yang kita temui selama proses pendampingan terdakwa yaitu susahnya komunikasi dengan terdakwa,kendala dalam keuangan atau dana, karena diperlukannya biaya atau dana untuk memanggil saksi ahli dalam pemeriksaan saksi dalam perkara tindak pidana. Disarankan kepada Advokat untuk melaksanakan pemberian bantuan hukum kendati penasihat hukum masih kurang atau belum memadai.Kata Kunci:  Hambatan Bantuan Hukum, Terdakwa, Peradilan Pidana